Faktor-Faktor yang Mempengaruhi Auditor Switching dengan Financial Distress sebagai Moderasi - Pitaloka, Herninda; Guritno, Agung (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2021)
This study aims to determine the Effect of KAP Reputation, Previous Year's Opinion and Firm Growth with Financial Distress as a Moderating Variable in Companies Listed in the Indonesian Sharia Stock Index (ISSI) 2019. The method of data collection is to collect annual financial reports (annual report) on IDX. and the company's official website. Obtained a sample of 280 companies with purposive sampling technique. The data was processed with IBM Statistics SPSS version 23. The analysis included descriptive statistical tests, model feasibility tests, classification matrix tests, the formation of logistic regression functions, partial parameter significance tests, simultaneous parameter significance tests, coefficients of determination tests and MRA tests. The results showed that the reputation of the KAP and the opinion of the previous year partially gave a positive and significant effect on auditor switching. The MRA test shows that financial distress cannot moderate KAP's reputation, previous year's opinion, and firm growth on auditor switching.